Complete Genome Sequence of a Livestock-Associated Methicillin-Resistant Staphylococcus aureus Sequence Type 5 Isolate from the United States - Hau, Samantha J. (Genome Announc, 2017)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) may be the largest MRSA reservoir outside the hospital setting. One concern with LA-MRSA is the acquisition of novel mobile genetic elements by these isolates. Here, we report the complete genome sequence of a swine LA-MRSA sequence type 5 isolate from the United States.